Selected Papers from IEEE ICKII 2019 - Meen, Teen-Hang; Zhao, Wenbing; Yang, Cheng-Fu (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book, entitled "Selected papers from IEEE ICKII 2019", selected 13 excellent papers from the 260 papers presented in the IEEE International Conference on Knowledge Innovation and Invention (IEEE ICKII) 2019 on energies. The 2nd IEEE ICKII 2019 was held in Seoul, South Korea, 12-15 July, 2019, and provided a unified communication platform for research on information technology, innovation design, communication science and engineering, industrial design, creative design, applied mathematics, computer science, electrical and electronic engineering, mechanical and automation engineering, green technology and architecture engineering, material science, and other related fields. The ICKII conference enables interdisciplinary collaboration of science and engineering technologists in the academic and industrial fields, as well as international networking. This book is a collection of 13 research papers. The fields included are as follows: energy fundamentals, energy sources and energy carriers, energy exploration, intermediate and final energy use, energy conversion systems, and energy research and development. The main goals of this book are to encourage scientists to publish their experimental and theoretical results in as much detail as possible, and to discover new scientific knowledge relevant to the topics of energies.